2020
DOI: 10.3390/ijerph17072382
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Spatiotemporal Trend Analysis of Human Brucellosis in China, 1950–2018

Abstract: The rate of brucellosis, a zoonotic disease, has rapidly increased in humans brucellosis(HB) in recent years. In 1950–2018, a total of 684,380 HB cases (median 2274/year (interquartile range (IQR) 966–8325)) were reported to the National Infectious Disease Surveillance System in mainland China. The incidence of HB peaked in 2014 (4.32/100,000), and then showed a downward trend; we predict that it will maintain a steady downward trend in 2019–2020. Since 2015, the incidence of HB has shown opposite trends in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…The results showed that the incidence rate of human brucellosis in the Hinggan League from 2004 to 2019 exhibited a significant increasing trend and imbalance in distribution among regions. The increasing trend in incidence rate of human brucellosis in this region coincides with previous studies [24], the rate of human brucellosis infection has rapidly increased in recent years. Tongliao City is one of the highest risk areas for human brucellosis in Inner Mongolia (China), as Tongliao city is geographically close to Hinggan League, incidence rates increased dramatically from 9.2/100 000 in 2007 to 69.2/ 100 000 in 2011, then decreased from 2012 to 2016; incidence rates rose again in 2017 to 44.3/100 000 [25].…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that the incidence rate of human brucellosis in the Hinggan League from 2004 to 2019 exhibited a significant increasing trend and imbalance in distribution among regions. The increasing trend in incidence rate of human brucellosis in this region coincides with previous studies [24], the rate of human brucellosis infection has rapidly increased in recent years. Tongliao City is one of the highest risk areas for human brucellosis in Inner Mongolia (China), as Tongliao city is geographically close to Hinggan League, incidence rates increased dramatically from 9.2/100 000 in 2007 to 69.2/ 100 000 in 2011, then decreased from 2012 to 2016; incidence rates rose again in 2017 to 44.3/100 000 [25].…”
Section: Discussionsupporting
confidence: 89%
“…2010, human brucellosis has occurred or reappeared in all provinces in southern China [27]. These data confirm that the geographic distribution of the disease has also evolved, with the movement of B. melitensis strains to the south.…”
Section: Discussionmentioning
confidence: 53%
“…The non-regulated animal trade has an important impact on the dissemination of brucellosis. Infected sheep and their products that have not been quarantined in the north before import to the south may be the main cause for the increasing incidence of human brucellosis in southern China [27]. Introduced infected sheep from northern regions may have led to a brucellosis outbreak epidemic in Zhejiang Province, China [32].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2011, 31 provinces in China have reported at least 35,000 human brucellosis cases annually, with more than 90% of these cases reported in northern China ( Wang et al, 2013 ). Nationwide, the incidence of human brucellosis shows an apparent geographic expansion from northern pastureland provinces to the adjacent grassland and agricultural areas, then to southern coastal and southwestern areas ( Guan, Wu & Huang, 2018 ; Yang et al, 2020 ). From 2005 to 2018, a total of 12,671 confirmed human brucellosis cases were reported in Shaanxi Province, with approximately 70.36% of cases reported in Shaanbei upland plateau, and the average annual incidence reached 11.50/100,000, which was higher than the national average incidence in 2018 (2.73/100,000) ( Peng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%